AN ANALYSIS OF THE PRIORITY NEEDS IN THE ACADEMIC MANAGEMENT DEVELOPMENT OF SECONDARY SCHOOLS UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE BANGKOK 1 ZONE 2 BASED ON THE CONCEPT OF METACOGNITIVE SKILLS - Meeyai, Meyhaporn; Chaemchoy, Sukanya (Journal of Educational Review Faculty of Education in MCU, 2024)
The objective of this research article is twofold: 1) to examine the current situation and desired state of academic management in secondary schools under the Secondary Educational Service Area Office Bangkok 1 Zone 2, based on the concept of metacognitive skills, and 2) to investigate an analysis of the priority needs in the academic management development of secondary schools under the Secondary Educational Service Area Office Bangkok 1 Zone 2, based on the concept of metacognitive skills. The research adopts a descriptive research approach. The research tools include questionnaires and statistical analysis methods such as frequency, percentage, mean, standard deviation, and modified Necessary Condition Analysis (PNIModified). The data are gathered from school administrators and teachers from all 14 secondary schools, totaling 280 individuals. The research findings reveal that 1) the current situation and desired state of academic management in the studied schools are categorized as moderate to the highest levels. In terms of metacognitive skills management and promotion, they also fall within similar levels. 2) The highest demand for development in academic management lies in the area of measurement and evaluation, while the area with the lowest necessary requirements is learning management.